Evaluating third- and fourth-year veterinary students' communication skills knowledge and performance at Colorado State University - Janke, Natasha; Shaw, Jane R; Coe, Jason B (Journal of the American Veterinary Medical Association, 2022)
To assess the impact of a communication program on a cohort of veterinary students' knowledge and performance of communication skills. Class cohort of veterinary students at Colorado State University. Year 3 students' knowledge of communication skills was evaluated using quizzes, administered before and after the fall 2016 and spring 2017 Clinical Communication Skills-I and II junior practicum. In year 4, student performance of 22 Calgary-Cambridge Guide communication skills was assessed by coding video-recordings of student-client interactions collected during their second and fourth weeks of the Community Practice rotation in the summer and fall of 2017 and spring of 2018. The impact of training, association with demographic factors, and correlation between knowledge and performance of communication skills were investigated. In year 3, 136 students completed both fall and spring quizzes; in year 4, 65 week-2 and 29 week-4 appointments were video-recorded during Community Practice rotation. Students' knowledge assessed via quizzes containing skill spotting and skill demonstrating questions increased significantly after the fall and spring junior practicums; however, knowledge of communication skills was not associated with performance during year 4 Community Practice rotations. Communication skills most frequently demonstrated by students during the fourth year Community Practice rotation were open-ended questions, closed-ended questions, empathy toward the client and patient, providing "chunks" of information, and signposting. Students received high quality scores for non-verbal behaviors and logical clinical interview structure. Results suggest that experiential learning techniques, including a flipped classroom approach, role-play, and communication laboratories contributed to increased student knowledge of communication skills.